Analysis of goals in European football and the most influential part in final standings - Francisco Daniel Martínez Martínez; Higinio González-García (Federación Extremeña de Balonmano; University of Extremadura, 2018)
The objectives of this work were: to know the differences of the scoring goals based on the minute and match period of the main European leagues: Spanish, English, French, German and Italian; and check in which period of the match are produced the most influential goals in final league classification. The sample was statistical data of 98 first division football teams of the 2016/2017 full season of the German, Spanish, French, English and Italian leagues. The results showed no statistical differences between the different European leagues in the record of goals scored depending on time and period of the match (p>.05), nor were found statistical differences when it was examined the first four classified teams of each league (p>.05) and even though, when the last four were examined (p>.05). The linear regression analysis showed that goals scored in minutes from "16 to 30" (p<.05) and in minutes from "31 to 45" (p<.05) indicated a relationship with having a greater position in the table. Therefore, it was shown that the minutes "16 to 30" and "31 to 45" may be the minutes of the game in which scoring goals may determine a higher position in the final classification.